Investigating morphological awareness and the processing of transparent and opaque words in adults with low literacy skills and in skilled readers. (25th August 2014) - To, Nancy L.; Tighe, Elizabeth L.; Binder, Katherine S.
Abstract : For adults with low literacy skills, the role of phonology in reading has been fairly well researched, but less is known about the role of morphology in reading. We investigated the contribution of morphological awareness to word reading and reading comprehension and found that for adults with low literacy skills and skilled readers, morphological awareness explained unique variance in word reading and reading comprehension. In addition, we investigated the effects of orthographic and phonological opacity in morphological processing. Results indicated that adults with low literacy skills were more impaired than skilled readers on items containing phonological changes but were spared on items involving orthographic changes. These results are consistent with previous findings of adults with low literacy skills reliance on orthographic codes. Educational implications are discussed.